(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, the tax system of the Republic of Uzbekistan and the role of indirect taxes, increasing the tax administration literacy of the population, supporting entrepreneurship, creating an equal competitive environment and guaranteeing the rights of consumers, and the hidden economy The improvement of administration based on the promotion of active participation of the general public in curbing is highlighted.